Մեսրոպ Մաշտոցի փիլիսոփայական հայացքները - Ս. Ս. Արևշատյան (ՀՀ ԳԱԱ հրատ.)
Создатель армянской письменности Месроп Маштоц (361—440 гг.) сыграл видающуюся роль во многих областях духовной культуры древней Армении. Он явился и первым мыслителем, создавшим философско-богословские труды, основоположником армянской патристики и апологетики. Mesrop Mashtots (361 — 440), the creator of the Aimenian alphabet, played a remarkable role in many spheres of the spiritual culture of ancient Armenia. Mashtots was alsо the first to create philosophical and theological works, i s well as the founder of the Armenian patristic and apologetics.
Keywords: History; Bibliography; B Philosophy; Psychology; Religion; Books; Writing; Paleography; B Philosophy; D History